The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.3325/cmj.2011.52.604
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions caused by drug-drug interactions reported to Croatian Agency for Medicinal Products and Medical Devices: a retrospective observational study

Abstract: AimTo analyze potential and actual drug-drug interactions reported to the Spontaneous Reporting Database of the Croatian Agency for Medicinal Products and Medical Devices (HALMED) and determine their incidence.MethodsIn this retrospective observational study performed from March 2005 to December 2008, we detected potential and actual drug-drug interactions using interaction programs and analyzed them.ResultsHALMED received 1209 reports involving at least two drugs. There were 468 (38.7%) reports on potential d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 50 publications
(65 reference statements)
0
24
0
2
Order By: Relevance
“…Original observational studies were included if they met the following criteria: (a) the identification of DDIs was performed by using a DDI electronic database; (b) clinically manifested DDI was confirmed by laboratory tests and/or signs and symptoms were documented in the medical records and analyzed by specialists [ 25 ]; (c) data for the calculation of the prevalence of clinically manifested DDIs among patients, prescriptions, or DDI adverse reaction reports were available; and (d) the study was published in English, Portuguese, or Spanish. In this systematic review, we excluded: (a) duplicate records; (b) studies with unavailable abstract or full-text, even after authors were contacted; and (c) studies focusing only on specific diseases/pharmacotherapies (for example: patients receiving oncological, HIV, or diabetes treatment) or specific drugs.…”
Section: Methodsmentioning
confidence: 99%
“…Original observational studies were included if they met the following criteria: (a) the identification of DDIs was performed by using a DDI electronic database; (b) clinically manifested DDI was confirmed by laboratory tests and/or signs and symptoms were documented in the medical records and analyzed by specialists [ 25 ]; (c) data for the calculation of the prevalence of clinically manifested DDIs among patients, prescriptions, or DDI adverse reaction reports were available; and (d) the study was published in English, Portuguese, or Spanish. In this systematic review, we excluded: (a) duplicate records; (b) studies with unavailable abstract or full-text, even after authors were contacted; and (c) studies focusing only on specific diseases/pharmacotherapies (for example: patients receiving oncological, HIV, or diabetes treatment) or specific drugs.…”
Section: Methodsmentioning
confidence: 99%
“…Observational studies examining actual DDIs were included if they were prospective or retrospective; the patients were of any age, admitted to hospital wards, or visited outpatients/emergency department due to DDIs; and studies were published in any language and provided sufficient data for calculating the prevalence rates. The actual DIs were defined on the basis of clinical evidence; that is, they were confirmed by laboratory tests or by symptoms . Potential DIs can be defined as documented interactions that may either enhance or antagonize the pharmacological activity of the drugs, resulting in potential adverse effects …”
Section: Methodsmentioning
confidence: 99%
“…Number and percent of the evaluated studies that failed to meet each of the methodological criteria tested, the number of the evaluated criteria not satisfied per country, and the number of studies that satisfied more than 4 criteria per country is presented in Table 2 . References of the analyzed studies from Bosnia and Herzegovina could be found in our previous publication ( 12 ), while the references of the studies analyzed from Croatian ( 17 - 59 ), Slovenian ( 60 - 92 ) and Serbian medical journals ( 93 - 135 ) are given on the list at the end of this article.…”
Section: Resultsmentioning
confidence: 99%